Expanding Brand Personality Congruence to Brand Personality Fit: The Importance of Customer Value Proposition as aModerating Fit on Brand Performance - Wirdamulia, Ardi; Afiff, Adi Zakaria (UI Scholars Hub, 2021)
This research demonstrates that brand performance can be enhanced not only through brand personality congruence with customer personality, but also through brand personality fit, namely the moderating fit of customer value proposition to brand personality. Through a study covering 125 brands, the result demonstrates that the moderating fit between brand personality and the different level of customer value proposition positively affects brand performance. Price-quality relationship for attribute-based customer value, self-construal for consequences-based customer value and self-regulatory focus as goal-based customer value are used to test this moderating fit relationship. Other findings show that this moderating fit is strongest toward the brand cognitive performance. Finally, the result of this study suggests marketers to incorporate the brand personality design into their positioning statement so that the overall customer value proposition can be developed in a more integrated manner, leading to higher brand performance